J-shaped relationship of serum neurofilament light chain with urinary albumin excretion in US adults: NHANES 2013–2014 - Yanting Liu; Qian Yang; Meiyun Zhang; Jingna Lin (Renal Failure)
Introduction This study focuses on investigating the relationship between serum neurofilament light chain (sNfL) and urinary albumin-to-creatinine ratio (uACR) among American adults aged 25–75.Methods An analysis was conducted on information gathered from 1741 individuals aged between 25 and 75 who participated in the National Health and Nutrition Examination Survey (NHANES) during the years 2013–2014. Generalized linear models were utilized, and restricted cubic spline (RCS) analysis was conducted to assess a non-linear relationship.Results Upon adjusting for multiple variables, a non-linear inverse J-shaped relationship was observed between sNfL and uACR. Compared with individuals in quartile 1 (Q1) of sNfL (2.8–8.3), those with quartile 4 (Q4) (≥19.1) had an adjusted β for uACR of 51.57.Conclusions The study found a J-shaped curve linking sNfL and uACR in American adults, with a turning point around log(sNfL) 2.928 pg/mL.